GSH Induced controlled release of levofloxacin from a purpose-built prodrug: luminescence response for probing the drug release in escherichia coli and staphylococcus aureus - Pal, Suman; Ramu, Vadde; Taye, Nandaraj; Mogare, Devraj G.; Yeware, Amar M.; Sarkar, Dhiman; Reddy, D. Srinivasa; Chattopadhyay, Samit; Das, Amitava (Bioconjugate Chemistry, 2016)
Fluoroquinolones are third-generation broad spectrum bactericidal antibiotics and work against both Gram-positive and Gram-negative bacteria. Levofloxacin (L), a fluoroquinolone, is widely used in anti-infective chemotherapy and treatment of urinary tract infection and pneumonia. The main pathogen for urinary tract infections is Escherichia colt, and Streptococcus pneumoniae is responsible for pneumonia, predominantly a lower respiratory tract infection. Poor permeability of L leads to the use of higher dose of this drug and excess drug in the outer cellular fluid leads to central nervous system (CNS) abnormality. One way to counter this is to improve the lipophilicity of the drug molecule, and accordingly, we have synthesized two new Levofloxacin derivatives, which participated in the spatiotemporal release of drug via disulfide bond cleavage induced by glutathione (GSH). Recent studies with Streptococcus mutants suggest that it is localized in epithelial lining fluid (ELF) of the normal lower respiratory tract and the effective [GSH] in ELF is similar to 430 mu M. E. coli typically cause urinary tract infections and the concentration of GSH in porcine bladder epithelium is reported as 0.6 mM for a healthy human. Thus, for the present study we have chosen two important bacteria (Gram + ve and Gram - ve), which are operational in regions having high extracellular GSH concentration. Interestingly, this supports our design of new lipophilic Levofloxacin based prodrugs, which released effective drug on reaction with GSH. Higher lipophilicity favored improved uptake of the prodrugs. Site specific release of the drug (L) could be achieved following a glutathione mediated biochemical transformation process through cleavage of a disulfide bond of these purpose-built prodrugs. Further, appropriate design helped us to demonstrate that it is possible also to control the kinetics of the drug release from respective prodrugs. Associated luminescence enhancement helps in probing the release of the drug from the prodrug in bacteria and helps in elucidating the mechanistic pathway of the transformation. Such an example is scarce in the contemporary literature.